General surgery postgraduate training in Malaysia: training curriculum version 1, 2021 - Roslani, April Camilla; Jarmin, Razman; Syed Abdul Aziz, Syed Hassan; Mohammad Amjad, Nasser; Lim, Kean Ghee; Hussein, Hanif (Majlis Dekan Fakulti Perubatan Universiti Awam, UM, 2021)
The National Postgraduate Medical Curriculum (NPMC) for General Surgery is the culmination of a collaboration between the General Surgery Conjoint Board, the Ministry of Higher Education (MOHE) and the Ministry of Health Malaysia, (MOH). It provides a structured and unified curriculum for the training of General Surgery specialists throughout the country aligned with the national strategy for healthcare. This standardisation of General Surgery specialist training for Malaysia will drive forward high quality, effective and safe patient care. All General Surgical training programmes in Malaysia should conform to the minimum requirements described in this document and subsequent editions when they become available. Every care has been taken to ensure that the information in this document was accurate at the time of publication. It is anticipated that the curriculum will be reviewed and revised at regular intervals, in keeping with advancements in surgical practice. Content may not be reproduced without permission from the authors.